Handel and the English Chapel Royal - Burrows, Donald, 1945- (Oxford studies in British church music., 2005)
Handel's English church music spans the complete period of his active career in London: his first anthem and the Utrecht Te Deum were composed soon after his arrival in London, and his last works nearly 40 years later. The repertory, which includes the Coronation Anthem Zadok the Priest, forms one of the most impressive and engaging areas of Baroque church music. Most of it was stimulated by Handel's creative contact with the English Chapel Royal, a group of; professional singers in a different tradition from the opera stars with whom he worked in the theatre.; This is the first full-length study of Handel's English Church music. As well as dealing with the many aspects of the compositions themselves, it traces the background to the diverse items in the repertory, which relates directly to Handel's constant but changing relationship with the Hanoverian British royal family, and was affected by political and dynastic events. It also examines the circumstances of Handel's performances, the building which (unlike his theatres) still survives in London; today.